Kemampuan olahraga dan aktivitas ekstrakulikuler pasukan baris berbaris dengan kecerdasan kinestetik - Lilis Madyawati; Ainun Rofiqoh; Rasidi Rasidi (Universitas Muhammadiyah Magelang, 2021)
This study aims to determine the relationship between sports ability and extracurricular activities of marching troops with kinesthetic intelligence of SDN Secang 1 students, Secang, Magelang Regency. The research used was correlational research method. The population in this study were students in I – VI grades. The sample in this study used purposive sampling, consisting of 98 students. The data collection method used a questionnaire. The data analysis technique in this study was used the simple linear regression and multiple regression data analysis. The results showed that there was a correlation between sports ability and extracurricular activities of marching troops with kinesthetic intelligence. This was evidenced by the acquisition of the coefficient of the Sports Ability variable with Kinesthetic Intelligence of 0.530, the extracurricular activity variable of Marching Forces with Kinesthetic Intelligence of 0.624. Based on this research, it can be concluded that the sports ability and extracurricular activities of the marching troops were correlated with kinesthetic intelligence.